Clinical predictors of disease progression in a cohort of Tunisian progressive Multiple Sclerosis - Souissi, A.; Mrabet, S.; Nasri, A.; Ben Djebara, M.; Gargouri, A.; Kacem, I.; Gouider, R. (Multiple sclerosis and related disorders, 2021)
•In North-Africa, MS exhibits particular characteristics that are mainly related to a more severe phenotype.•SPMS and PPMS share common features like age at onset of progression and faster disability rates but differ according to gender and first-relapse characteristics.•Median time to reach SPMS is faster for North Africans than Caucasians. Knowledge about progressive Multiple Sclerosis (MS) is mainly based on Caucasian studies. In our North-African context, MS exhibits particular characteristics that are mainly related to a more severe phenotype. Given the limited data available, there is an imminent need to characterize progressive MS in our latitudes. To describe the specificities of progressive MS and identify the inherent clinical predictors of disability accrual with a Tunisian cohort. A retrospective, hospital-based study was conducted in the department of neurology of Razi hospital. Patients, who had been diagnosed with MS, were divided into relapsing MS (RRMS), secondary progressive MS (SPMS) and primary progressive MS (PPMS). Epidemiological, clinical and paraclinical data were compared among the three groups. Of the 504 patients, a progressive MS was described among 115 patients. This percentage of (22.8%) is divided into 13.9% SPMS and 8.9% PPMS. During the first clinical attack, motor symptoms have revealed to be predominant during PPMS (91.1%). For SPMS onset, the median time was 10 years, and was significantly delayed for patients with visual onset or full recovery from the first relapse. Patients with progressive MS exhibited a more rapid disability accumulation. Compared to Caucasians, Tunisians exhibited a faster rate of conversion to SPMS. According to our natural progressive MS history, early clinical features are predictors of MS disability accrual.